GAGASAN PENDIDIKAN HUMANIS RELIGIUS ABDURRAHMAN MAS’UD - Nastiti, Ayem (Muhammadiyah University Press, 2020)
Abdurrahman Mas'ud is one of the figures who has several new ideas, one of which is developing religious humanist education as a criticism of traditional education that is taking place today. This idea is based on the problems of Islamic education in Indonesia which are still tinged with acts of violence against students. Data from the National Commission on Violence against Women for the past five years shows that 51 cases of violence have occurred in education in Indonesia. In detail, this study aims to describe the concept of religious humanist and religious humanist education according to Abdurrahman Mas'ud. This research is a type of library research with a biographical-qualitative approach. The data source of this research comes from the writings of the character directly, and as a support, it uses the writings of others that discuss the character. The results showed that the religious humanist concept of Abdurrahman Mas'ud, namely religious teachings that call on humans to do human things that are still based on religion as a form of carrying out the responsibility to God and also a responsibility to fellow humans. Meanwhile, religious humanist education is an educational process that provides opportunities for students to develop their abilities as social beings and religious beings who are guided by Islamic religious values to develop scientific abilities while remaining based on religious values.